Facile hydrothermal bio‐synthesis of cellulose acetate templated CuS nanorods like fibres: antibacterial, cytotoxicity effects and DNA cleavage properties against A549 lung cancer cells. Issue 1 (17th October 2019) - Manikandan, T.; Padmalaya, G.; Mahalakshmi, S.; Nivethitha, A.S.; Pavithran, V.; Perumal, S.; Sreeja, B.S.; Senthil Kumar, P.
Abstract : In this research, the hydrothermal method was used for synthesising cellulose acetate (CA) templated nanorods like CuS fibres using vegetable extract ( Brassica oleracea var. italica ). These extracts act as a reducing agent in the presence of CA. Surprisingly, when the same reaction was carried out in the absence of CA and broccoli extract, structural morphology disappeared and was found as agglomerated. In the presence of cellulose templated extract mediated CuS has revealed as nanorods like fibres and was confirmed by field emission scanning electron microscope analysis. Their crystallinity property of CuS nanoparticles (NPs) and cellulose templated biosynthesised CuS NPs was analysed and compared using X‐ray diffraction technique. The biological activities of the obtained product were examined for antibacterial assessment against two bacterial strains that include two‐gram negative strains ( E.Coli and S. aureus ). The nanostructured product found to exhibit excellent antibacterial agent against all the strains. Biosynthesised nanostructure showed its efficacy against A549 lung cancer cells which might attribute to a larger surface to volume ratio of nanorods like fibres. The authors observation suggest that CuS nanorods like fibres can significantly reduce the cell growth with IC50 value of 31.2 μg/ml.